1984
DOI: 10.1039/c39840001295
|View full text |Cite
|
Sign up to set email alerts
|

Dioxododecaisopropoxytetratungsten. Oxygen atom abstraction from acetone in reactions with hexaisopropoxyditungsten (WW)

Abstract: WJOPri)6(py)2( W:W) (py = pyridine) and acetone (1 equiv.) react in hydrocarbon solvents at ambient temperatures to yield tetramethylethylene and W402(OPri)12 the latter of which is shown, by an X-ray study, to be an unusual cluster type in which the eight electrons available for M-M bonding are partitioned into an M-M triple and M-M single bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The W2(0-i-Pr)6(py)2 compound with a tungsten-tungsten triple bond has been shown to couple acetone to 2,3-dimethyl-2-butene with the resulting formation of W402(0-i-Pr)12. 80 The tungsten complex here effects the oxygen extrusion from acetone, but the exact mechanism is not clear. plex, which has been structurally characterized, is an excellent model for the postulated intermediate in the reactions of McMurry (although the heterogeneous titanium systems may not contain metal-metal bonds).…”
Section: B Zirconium and Hafniummentioning
confidence: 98%
“…The W2(0-i-Pr)6(py)2 compound with a tungsten-tungsten triple bond has been shown to couple acetone to 2,3-dimethyl-2-butene with the resulting formation of W402(0-i-Pr)12. 80 The tungsten complex here effects the oxygen extrusion from acetone, but the exact mechanism is not clear. plex, which has been structurally characterized, is an excellent model for the postulated intermediate in the reactions of McMurry (although the heterogeneous titanium systems may not contain metal-metal bonds).…”
Section: B Zirconium and Hafniummentioning
confidence: 98%
“…Wiberg found E (P=C)=+3.0 kJ/mol at the MP2(fc)/6‐31+G(d) level [77] . Schoeller has apparently calculated the Z (P=C) form in a communication, but no details are provided [78,79] . In more recent work, Schoeller has only considered the E (P=C) isomer [80] as has Chernega [81] .…”
Section: Resultsmentioning
confidence: 99%
“…In a chance reaction between W 2 (O i Pr) 6 (py) 2 and acetone‐d 6 in a NMR tube the black crystalline compound W 4 O 2 (O i Pr) 12 (py) was discovered 16. The source of the oxygen was traced to the acetone when, in a study of the protio species, we identified Me 2 C=CMe 2 as being the other product.…”
Section: Resultsmentioning
confidence: 99%